A importância da arte na inclusão escolar e no desenvolvimento de pessoas com necessidades educativas especiais: deficiência intelectual - Oliveira, Uillian Trindade (2012)
This research aims to understand and analyze what is the importance of art in the development of people with Intellectual Disabilities regarding aspects within an inclusive school. To support our studies and understand better the context of research, seek grants in the theories of Vygotsky on the social-historical approach. This is an ethnographic case study of two students with ID, Anita (pseudonym) 12 years old and Candido (pseudonym) 14 years old. This dissertation aims to investigate how art can help people with special needs, specifically with Intellectual Disabilities. We will do the daily analysis of two students with ID at a Municipal School of Basic Education in Cariacica, ES. We observed the relationships of students surveyed with the discipline of art, also their production in the classroom, relationships with colleagues and with the art teacher. Considering that social relationships contribute to the development of people with ID and that art can contribute to their personal development dialogues seek Atack (1995), Lowenfeld (1977), Reily (2004), Read (1986), Vygotsky (2001) among others. From the data collected through participant observation in the classroom, interviews, field recordings, audio recordings, photographic records, as well as the written transcript of the speech of students and teacher during activities in the classroom, these elements will be of great relevance to the analysis, which will dialogue with the authors mentioned. Although we makes considerations about social inclusion, inclusive schooling, intellectual disability and the relationship of people with special needs with Art.